2022
DOI: 10.1055/s-0042-1755269
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of persistent headache attributed to past stroke

Abstract: Background Persistent headache attributed to past stroke (PHAPS) is a controversial entity, recently included in the third edition of the International Classification of Headache Disorders (ICHD-3) despite being described only in retrospective studies. Objective To determine the frequency and characteristics of PHAPS in patients admitted with acute stroke. Methods We selected all patients with headache associated with acute stroke (HAAS) from a prospective, single-center registry of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 45 publications
(83 reference statements)
2
6
0
Order By: Relevance
“…Many of them jointly assessed patients with IS and hemorrhagic stroke, thereby not enabling an adequate comparison with our results. 4,6,9,17,18 The only study that was methodologically comparable with ours, which only included patients with IS and used the criterion diagnosis of ICHD-3, reported an incidence of 10.4%, which is similar to the present study. 10 Even if we were to disregard the losses and use the total sample, the incidence would still be considered high (5.4%).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Many of them jointly assessed patients with IS and hemorrhagic stroke, thereby not enabling an adequate comparison with our results. 4,6,9,17,18 The only study that was methodologically comparable with ours, which only included patients with IS and used the criterion diagnosis of ICHD-3, reported an incidence of 10.4%, which is similar to the present study. 10 Even if we were to disregard the losses and use the total sample, the incidence would still be considered high (5.4%).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have reported a frequency of headache in the late phase of stroke ranging from 7% to 51%. [4][5][6][8][9][10]17,18 These studies have used different methodologies, diagnostic criteria, and assessment intervals of patients after stroke, which ranged from 3 months to 3 years. Many of them jointly assessed patients with IS and hemorrhagic stroke, thereby not enabling an adequate comparison with our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations